AKTIVITAS FISIK AKUT INTENSITAS TINGGI MEMPERBAIKI KADAR IL-6 OTOT MODEL MENCIT DIABETES MELITUS - Purwoto, Septyaningrum Putri; Purwanto, Bambang; Liben, Paulus (Universitas Tribhuwana Tunggadewi, 2020)
Diabetes mellitus is a metabolic disease whose prevalence continues to increase. Diabetes mellitus sufferers are advised to do lifestyle interventions in the form of physical activity. Physical activity provides benefits for diabetics, through the autocrine response of muscles to release IL-6 for muscle repair. The purpose of this study was to determine the appropriate intensity of physical activity against muscle IL-6 in diabetic mice. The subjects in this study were male mice (balb / c) weighing 20-30 grams. This study was divided into 4 groups. The treatment in the form of treadmill activity is carried out once with heating for 5 minutes and core for 30 minutes. This study used a True Experimental research design using a Random Control Group Posttest-Only Design research design. The variable measured in this study was muscle IL-6, namely the calf muscle (gastrocnemious and soleus muscles) of the left and right legs of each subject 24 hours after acute physical activity. Acute physical activity causes the release of interleukin-6 by myofibers. Based on the analysis results showed that there was a significant effect of low, medium, and high intensity acute physical activity on muscle IL-6 levels (p = 0.05). In addition, it also showed that the highest average muscle IL-6 level was the high intensity treatment group with a value of 325.17267 mg / dL. These results prove that high-intensity acute physical activity improves IL-6 levels in the muscle muscle model of diabetes mellitus mice.